2021
DOI: 10.1186/s12891-021-04035-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful recovery following musculoskeletal trauma: protocol for a qualitative study of patients’ and physiotherapists’ perceptions

Abstract: Background Annually in the UK, 40,000–90,000 people are involved in a traumatic incident. Severity of injury and how well people recover from their injuries varies, with physiotherapy playing a key role in the rehabilitation process. Recovery is evaluated using multiple outcome measures for perceived levels of pain severity and quality of life. It is unclear however, what constitutes a successful recovery from injury throughout the course of recovery from the patient perspective, and whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Constant comparative analysis took place, beginning after transcription of the first focus group and continued throughout data collection (47). A similar sample size has been used in previous research and allowed for the collection of a rich description from participants regarding RRIs (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Constant comparative analysis took place, beginning after transcription of the first focus group and continued throughout data collection (47). A similar sample size has been used in previous research and allowed for the collection of a rich description from participants regarding RRIs (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to expected research from the Netherlands [56], recommendations for future research is currently being addressed by two further study protocols [61,62]. Soberg et al [61] aims to quantitatively and prospectively investigate rehabilitation needs, services and functional outcomes in geographical regions with cost consideration to target future rehabilitation provision [61].…”
Section: Future Research Pathwaysmentioning
confidence: 99%
“…Soberg et al [61] aims to quantitatively and prospectively investigate rehabilitation needs, services and functional outcomes in geographical regions with cost consideration to target future rehabilitation provision [61]. Conducting semi-structured interviews and focus groups, Middlebrook et al [62] aims to explore views and perceptions of successful recovery. Once completed and published these studies could provide much needed research into rehabilitation geographical variation and show the areas for development to meet NICE guidelines [20].…”
Section: Future Research Pathwaysmentioning
confidence: 99%
“…Teo et al [ 11 ] shared factors affecting patient engagement in exercise rehabilitation, noting that exercise programs are best co-designed between patients and exercise specialists with individual consideration of engagement factors to optimize participation and outcomes. Middlebrook et al [ 12 ] delved further into improving musculoskeletal trauma recovery outcomes by evaluating patients' and physiotherapists' successful recovery perceptions to ensure alignment. Salmasi et al [ 13 ] reported on researchers' perspectives in an OMERACT adherence study, while Cornelissen et al [ 14 ] shared a co-designed multi-component adherence protocol for osteoporosis care.…”
Section: Introductionmentioning
confidence: 99%